1961
DOI: 10.1007/bf02633904
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage temperature and antioxidant treatment on the chemical and nutritive characteristics of herring meal

Abstract: The effects of storage temperature and antioxidant treatment on the chemical and nutritive properties of herring meal were studied. The following observations were made: Low‐temperature (−20°C.) storage promoted more rapid decrease in ether extractability and in iodine value of the ether extract than did storage at 25.5°C. Antioxidant treatment prevented the decrease both in ether extractability and iodine value of the extract. Binding of the lipid into a complex from which the lipid was extractable with aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1962
1962
1992
1992

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It was reported previously (March et al, 1960) that BHT-treatment of herring meals retarded the decrease in both ether-extractability and iodine value of the extract. This stabilizing effect of BHT was also apparent in the present test.…”
Section: Resultsmentioning
confidence: 95%
“…It was reported previously (March et al, 1960) that BHT-treatment of herring meals retarded the decrease in both ether-extractability and iodine value of the extract. This stabilizing effect of BHT was also apparent in the present test.…”
Section: Resultsmentioning
confidence: 95%
“…In a rather different context, Banks (1950) and other workers (Lea, Parr and Carpenter, 1958;March et al, 1961) showed that autoxidation of the fats in dehydrated herrings and herring meal proceeds faster at lower temperatures than at higher temperatures. Thus Lea et al (1958) found the rate faster at 10°C than at 37"C, Banks (1950) found it faster at 0°C than at 25°C and March et aZ.…”
Section: (A) Oxidation Of Fats In the Presence Of Amines And Other Comentioning
confidence: 96%